Queer Representation and Public Pedagogy in American Musical Theatre - Craig M. McGill; Alan J. Chaffe; Kyle W. Ross (Adult Education Research Conference, 2022)
This paper explores the Broadway musical as a site of queerness and queer representation through the lens of queer public pedagogy.
Keywords: Broadway musical; queer public pedagogy; queer theatre; queer identity